2018
DOI: 10.1007/s12272-018-1048-9
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-inflammatory activity of compounds from the rhizome of Cnidium officinale

Abstract: Five new compounds, 9,3'-dimethoxyhierochin A (1), 6-oxo-trans-neocnidilide (2), (±)-(3E)-trans-6-hydroxy-7-methoxydihydroligustilide (3), (±)-cnidiumin (4), and 6-(1-oxopentyl)-salicylic acid methyl ester (5), together with twenty known compounds (6-25), were isolated from the rhizome of Cnidium officinale. The chemical structures of new compounds were established by NMR spectroscopic techniques, mass spectrometry, Mosher's method, and CD spectrum. Their anti-inflammatory activities were evaluated against lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…The functional effects of CO as a natural product were verified in our study [25,27]. The antioxidant activity of the natural extracts can be attributed to various components, particularly the total phenolic and flavonoid content present in the extracts [19,27]. These results can be related to phenolic compounds such as polyphenols and flavonoids [27] that exhibit antibacterial activity [21].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The functional effects of CO as a natural product were verified in our study [25,27]. The antioxidant activity of the natural extracts can be attributed to various components, particularly the total phenolic and flavonoid content present in the extracts [19,27]. These results can be related to phenolic compounds such as polyphenols and flavonoids [27] that exhibit antibacterial activity [21].…”
Section: Discussionsupporting
confidence: 61%
“…The rhizome of CO has various pharmacological effects, such as antibacterial, antifungal, angiogenic, and sedative properties [15][16][17]. In addition, studies on aerial parts as well as rhizomes of CO have also reported its ability to detoxify oxidizing substances and other toxic substances generated in the body, its inhibitory activity towards mutations leading to cancer, and its antifungal activity against phytopathogenic fungi [18][19][20][21]. Accordingly, CO is known to have antibacterial activity against various microorganisms, such as bacteria and fungi; however, there is a paucity of research on its effects on oral microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Exact structure: found in the roots of Angelica sinensis (AS) (Deng et al 2006), anti-inflammatory activity (Tran et al 2018), act as synergistic calcium antagonists for the treatment of coronary heart disease (Lei et al 2018), cytotoxic activity against MCF-7 (breast cancer), NCI-H187 (lung cancer) and KB cells (Wisetsai et al 2018), act as pancreatic lipase inhibitor for treatment of obesity (Mo et al 2016), used for the treatment of peptic ulcer (Chung et al 2005), used for the treatment and prevention of diabetes mellitus (D'orazio et al 2007)…”
Section: Resultsmentioning
confidence: 99%
“…Similar structure: free radical scavenging activity (Adil et al 2018), active component of Angelica sinensis (AS) herb, used as the blood-nourishing tonic (Chen et al 2017), anti-inflammatory activity (Tran et al 2018), antioxidant and antibacterial activity against Bacillus subtilis , Staphylococcus aureus , Escherichia coli , Pseudomonas aeruginosa , Klebseilla pneumonia , Agrobacterium tumefaciens and antifungal activity against Candida albicans , Mucor sp., Aspergillus flavus , Penicilium expansum (Ksouri et al 2017), neuroprotective effect on PC12 cells (Lu-Si et al 2017), used to treat bone diseases (Wang et al 2017a, b), prevents cancer by increase the oxygen release efficiency of Hb (Wang and Chen 2017), neuroprotective and anticancer effects against lung (A549), human colon carcinoma (HCT-8), and hepatocarcinoma (HepG2) cancer cell (Gong et al 2016)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation